FET690 : Art curatorship / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2021)
The course introduces the students creating art exhibitions. It examines the procedures of creating and marketing exhibition of both historical and contemporary art. It also provide guidance for the students on how to plan, organize manage and assess educational programmes and equips students with the basic knowledge and information necessary to develop their own educational events and programming strategies.